Neuroprotective Effects of AMP-Activated Protein Kinase on Scopolamine Induced Memory Impairment - Kim, Soo-Jeong; Lee, Jun-Ho; Chung, Hwan-Suck; Song, Joo-Hyun; Ha, Joohun; Bae, Hyunsu (The Korean journal of physiology & pharmacology, 2013)
AMP-activated protein kinase (AMPK), an important regulator of energy metabolism, is activated in response to cellular stress when intracellular levels of AMP increase. We investigated the neuroprotective effects of AMPK against scopolamine-induced memory impairment in vivo and glutamate-induced cytotoxicity in vitro. An adenovirus expressing AMPK wild type alpha subunit (WT) or a dominant negative form (DN) was injected into the hippocampus of rats using a stereotaxic apparatus. The AMPK WT-injected rats showed significant reversal of the scopolamine induced cognitive deficit as evaluated by escape latency in the Morris water maze. In addition, they showed enhanced acetylcholinesterase (AChE)-reactive neurons in the hippocampus, implying increased cholinergic activity in response to AMPK. We also studied the cellular mechanism by which AMPK protects against glutamate-induced cell death in primary cultured rat hippocampal neurons. We further demonstrated that AMPK WT-infected cells increased cell viability and reduced Annexin V positive hippocampal neurons. Western blot analysis indicated that AMPK WT-infected cells reduced the expression of Bax and had no effects on Bcl-2, which resulted in a decreased Bax/Bcl-2 ratio. These data suggest that AMPK is a useful cognitive impairment treatment target, and that its beneficial effects are mediated via the protective capacity of hippocampal neurons.